2017
DOI: 10.2217/bmm-2016-0308
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin: Its Potential Role in Cancer of Children and Young Adults

Abstract: The literature review suggests that OPN may play important roles in the development and progression of selected cancers of children and young adults, including acute lymphoblastic leukemia, malignant gliomas, AT/RT and Langerhans cell histiocytosis. However, limited number of published studies prevents from definite concluding on the clinical utility of OPN as a marker of diagnosis, prognosis and treatment monitoring in these pediatric cancers. Further studies performed in more numerous groups of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…OPN gene is upregulated in primary central nervous system lymphomas (PCNSL) as compared to that in diffuse large B cell lymphoma (DLBCL) [208], and its levels in cerebrospinal fluid (CSF) appear to be an independent predictor of shorter progression-free and overall survival [209]. Serum levels of OPN also predict response to therapy and survival in DLBCL [210, 211] and serum and CSF levels were correlated to tumor bulk and response to therapy in children with acute lymphoblastic leukemia (ALL) [211]. Expression of OPN is increased in both bone marrow blasts and serum of patients with acute myeloid leukemia (AML), and high-OPN mRNA expression independently predicts overall survival ( p = 0.025), especially in low-intermediate risk forms [212].…”
Section: Osteopontin In Hematopoietic and Lymphoid Tumorsmentioning
confidence: 99%
“…OPN gene is upregulated in primary central nervous system lymphomas (PCNSL) as compared to that in diffuse large B cell lymphoma (DLBCL) [208], and its levels in cerebrospinal fluid (CSF) appear to be an independent predictor of shorter progression-free and overall survival [209]. Serum levels of OPN also predict response to therapy and survival in DLBCL [210, 211] and serum and CSF levels were correlated to tumor bulk and response to therapy in children with acute lymphoblastic leukemia (ALL) [211]. Expression of OPN is increased in both bone marrow blasts and serum of patients with acute myeloid leukemia (AML), and high-OPN mRNA expression independently predicts overall survival ( p = 0.025), especially in low-intermediate risk forms [212].…”
Section: Osteopontin In Hematopoietic and Lymphoid Tumorsmentioning
confidence: 99%
“…Here OPN in blood plasma might have a prognostic and predictive value on pediatric patients with traumatic brain injuries 21 . However, the potential of OPN as a biomarker in pediatric cancer patients is well accepted 22 …”
Section: Introductionmentioning
confidence: 99%
“…High tumor OPN expression was reported to correlate with higher grade, stage and shorter relapse-free survival and overall survival in adult STS (Bache et al 2010 ). In pediatric cancers, the tumor expression of OPN was examined in leukemias, lymphomas, Langerhans cell histiocytosis, central nervous system (CNS) tumors, osteosarcoma and renal tumors (summarized by Karpinsky et al 2017 ). To date, there has been no study on the prognostic role of this marker in children with MPNST or other STS subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of all publications on the role of OPN in cancers of children and young adults has shown that the monitoring of OPN protein level in serum and cerebral-spinal fluid of children with acute lyphoblastic anemia with CNS involvement and in patients with highly malignant brain tumors, reflected the tumor bulk and the response to CHT (Karpinsky et al 2017 ). To date, there have been no publications on the impact of OPN expression on response to naCHT in patients with STS.…”
Section: Discussionmentioning
confidence: 99%